Comparison of Aesthetic Plastic Surgery Laws Applied in the United States and Indonesia - Endang Sri Sarastri; Liliana Tedjo Saputro; MC Inge Hartini (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
Advances in science and technology in the field of aesthetic plastic surgery today no longer aims to treat but is used to change a person in supporting his appearance. The authority to carry out these medical procedures belongs to the Reconstructive and Aesthetic Plastic Surgeon Specialist (Dr. SpBP-RE), but the results of the medical actions carried out by Dr. SpBP-RE are not necessarily in accordance with the wishes of the patients. In order to avoid disputes between Dr. SpBP-RE and its patients and how to deal with it, the laws that apply in every country in the field of medicine, especially aesthetic plastic surgery, must be clear and firm. This study aims to find out and analyze the laws that apply in the field of aesthetic plastic surgery in Indonesia and in the United States so that the results can be theoretically and practically useful in overcoming medical malpractice. The type of research used was